Experimental Study and Seismic Response Evaluation of Chlorobutyl Rubber-Based Viscoelastic Dampers - Roshan-Tabari, Farnoosh; Toopchi-Nezhad, Hamid; Hashemi-Motlagh, Ghodratollah (Shock and Vibration, 2024)
Conventional viscoelastic devices often use high-damping elastomeric pads, typically made of patented formulations, that are bonded to steel plates. The response properties of these pads under cyclic shear deformations directly influence the load-deformation hysteretic response of the device. Chlorobutyl (CIIR) is a high-damping rubber commonly used in industrial applications. However, this study found that the damping properties of a typical CIIR rubber compound are insufficient for effective structural seismic mitigation at ambient temperatures above 0°C. The goal of this study was to develop a new composite of CIIR, referred to as modified CIIR, with improved damping properties and to compare its performance with that of the reference CIIR rubber. In the first phase of the experimental studies, the viscoelastic characteristics of the reference and modified CIIR rubber materials were evaluated using dynamic mechanical thermal analysis (DMTA) in tension mode. Prototype viscoelastic damper devices were then fabricated from both the reference and modified CIIR rubber materials and subjected to cyclic shear tests at room temperature and various loading frequencies. The results showed that the modified CIIR rubber exhibited significantly improved effective damping compared to the reference CIIR. The final component of this study involved investigating the seismic response of a 2D frame structure equipped with prototype dampers made from both reference and modified CIIR materials, using nonlinear time-history analyses. The analysis results indicated that the modified CIIR rubber can be effectively utilized in the seismic response mitigation of structures.